Shedding Light on the Convoluted Terrain of Differentiated Instruction (DI): Proposal of a DI Taxonomy for the Heterogeneous Classroom - Pozas Marcela; Schneider Christoph (De Gruyter, 2019)
Student heterogeneity is not limited to performance, but encompasses cultural background, language competence, learning styles, and motivation. Thus, heterogeneity inherently changes the demands placed on teachers and requires them to practice differentiated instruction (DI). However, existing DI frameworks tend to describe single exemplary DI practices and widely lack an empirical view. Thus, these frameworks may provide little help to classroom teachers when it comes to the question of how or by which instructional arrangements they can address student heterogeneity in their everyday classroom teaching. In an attempt to bridge the gap between educational theory and everyday instructional practice, this theoretical paper focusing on differentiation within secondary school education proposes a comprehensive taxonomy of the DI practices known in the literature and practice. Outlines for future research on DI are discussed.